Stellenbosch Safari : a multimedia program based on suggestopedic principles for the teaching of Afrikaans to international students at Stellenbosch University - Tredoux, Francois (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Afrikaans and Dutch))—University of Stellenbosch, 2007.